1987
DOI: 10.2307/2409260
|View full text |Cite
|
Sign up to set email alerts
|

Sex Allocation and Outcrossing Rate: A Test of Theoretical Predictions Using Bromegrasses (Bromus)

Abstract: Predictions of sex-allocation theory were tested by comparisons among hermaphroditic bromegrass (Bromus) species that differed in outcrossing rate. Relative maternal and paternal investment were calculated using both the ratio of pollen to seed production, and absolute allocations in units of energy, nitrogen, phosphorus, potassium, magnesium, and calcium. Outcrossing rate had a large effect on sex allocation; species having greater outcrossing rates had relatively more paternal reproductive effort. Bromus ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…All variation was observed as single-banded electrophoretic variants attributed to allozymes, indicating that selfing is characteristic of all diploids examined. This is in accordance with other data on autogamy and self-fertilization of Genea bromes (SMITH 1970;MCKONE 1985MCKONE , 1987NO-VAK et al 1991).…”
Section: Resultssupporting
confidence: 93%
“…All variation was observed as single-banded electrophoretic variants attributed to allozymes, indicating that selfing is characteristic of all diploids examined. This is in accordance with other data on autogamy and self-fertilization of Genea bromes (SMITH 1970;MCKONE 1985MCKONE , 1987NO-VAK et al 1991).…”
Section: Resultssupporting
confidence: 93%
“…ductive assurance in autogamous selfers also reduces the benefit of attractive structures for female fitness, as pollinators are not required for fertilization. Studies ofpollenovule ratios (Cruden, 1977;Preston, 1986;Vasek and Weng, 1988), male allocation (Schoen, 1982;Cruden and Lyon, 1985;Charnov, 1987;McKone, 1987), and allocation to attraction (Ritland and Ritland, 1989;Lyons and Antonovics, 1991) confirm the broad-scale patterns predicted for selfing and outcrossing taxa. However, few studies have measured both sex allocation and mating system in closely related, co-occurring taxa.…”
mentioning
confidence: 59%
“…Most studies, however, use biomass alone as an estimate of reproductive allocation, which may be problematic if tissues differ greatly in their building costs. However, McKone (1987) found that estimates of sex allocation in several grass species were quite robust when different resource currencies were used (i.e. energy content and ®ve different nutrients).…”
Section: Overall Sex Allocationmentioning
confidence: 99%